Tracking continuous positive airway pressure adherence in obstructive sleep apnea patients before, during, and after the COVID-19 lockdown - Abdulaziz O. BaHammam; Fawaz Alhuqayl; Ibrahim Alzaid; Ziyad Alzammam; Faisal Alhuqayl; Bader Rajeh; Galal Eldin Abbas Eltayeb; Samar Nashwan; Salih Aleissi; Ahmed Salem BaHammam (Annals of Thoracic Medicine)
BACKGROUND: This study aimed to examine the impact of the COVID-19 lockdown on adherence to continuous positive airway pressure (CPAP) therapy among Saudi patients with obstructive sleep apnea (OSA). It also sought to assess the influence of demographic variables and comorbidities on CPAP adherence. METHODS: A prospective cohort study was conducted at the University Sleep Disorders Center at King Saud University Medical City. The study included 67 OSA patients who exclusively used CPAP for treatment across three distinct intervals: prelockdown, during lockdown, and postlockdown. Adherence to CPAP therapy was objectively measured using “mask-on on-time monitoring” data from the CPAP machines. RESULTS: The study found a significant decrease in the number of days with CPAP usage during the lockdown period, which persisted postlockdown. Approximately half of the patients adhered to CPAP treatment throughout the three study intervals. The decrease in CPAP usage days during lockdown was particularly noticeable among patients younger than 50 and older than 65 years of age. The presence of comorbidities, body mass index, and sex did not significantly influence CPAP treatment adherence. CONCLUSION: The COVID-19 lockdown significantly impacted CPAP treatment adherence among OSA patients, with a decrease in adherence persisting postlockdown. This highlights the need for interventions to support CPAP adherence during challenging times such as a pandemic. Further research is needed to understand the long-term effects of the pandemic on CPAP therapy adherence.